Geochemistry and Holocene Sedimentary Environment Evolution of Subaqueous Clinoform off Shandong Peninsula (Yellow Sea) - Yingtao Zhu (MDPI AG, 2021)
As a key sedimentary body connecting the north and South Yellow Sea, the subaqueous clinoform off Shandong Peninsula plays an important role in the sedimentary system of China seas, and it is also a studied example in the study among the major “source to sink” systems. Based on AMS 14C dating, sediment grain size, major and trace element contents from core WH-05 located at the edge of the clinoform, we discuss changes in the deposition rate, analyze sediment provenance and controlling factors, and reveal the environmental evolution of the source area since the Holocene. Results from core WH-05 show that marine sedimentation began at about 8.5 ka B.P. The deposition rate decreased from the initial 28.37 m/ka to 0.52 m/ka. Sediment provenance suggests that the Huanghe river sediments have been the main source for the study area since the Holocene. The As/Al, V/Sc indicators show that the environmental oxidation environment was gradually weakened and then increased slightly starting from 7.0 ka B.P. The change in redox is consistent with the change in sea level, the deposition rate, and depositional depth.